Global political ties and the global financial cycle - Gene Ambrocio; Iftekhar Hasan; Xiang Li (Bank of Finland, 2024)
We study the implications of forging stronger political ties with the US on the sensitivities of stock returns around the world to a global common factor - the global financial cycle. Using voting patterns at the United Nations as a measure of political ties with the US along with various measures of the global financial cycle, we document evidence indicating that stronger political ties with the US amplify the sensitivities of stock returns in developing countries to the global financial cycle. We explore several channels and find that a deepening of financial linkages along with a reduction in information asymmetries and an amplification of sentiment are potentially important factors behind this result.
urn:nbn:fi-fe202401102232
Keywords: E44; F30; F50; G15; 330; Political Ties; Global Financial Cycle; International Spillovers; Stock returns